2011
DOI: 10.1186/1743-422x-8-281
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B virus genotypes in HBsAg positive individuals of Afghanistan

Abstract: BackgroundThe structural and functional differences between hepatitis B virus (HBV) genotypes are the mainstay to severity, complications, treatment and possibly vaccination against the virus. This study was conducted to determine the HBV genotypes in HBsAg positive patients of Afghanistan as no such large scale data available previously.MethodsTwo hundred and fourteen HBsAg-positive patients were included in this study. All patients were anti-HCV and anti-HIV negative. All the samples were confirmed for HBV D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…The most prevalent genotype in Iran is D1, and this is the first report of subgenotype D4 from Iran. This could be due to neighboring with Afghanistan; there is a heterogeneous distribution of HBV in Afghanistan . Although, in previous studies non‐DI subgenotypes, such as D2 and D3, have been rarely reported from Iran …”
Section: Discussionmentioning
confidence: 97%
“…The most prevalent genotype in Iran is D1, and this is the first report of subgenotype D4 from Iran. This could be due to neighboring with Afghanistan; there is a heterogeneous distribution of HBV in Afghanistan . Although, in previous studies non‐DI subgenotypes, such as D2 and D3, have been rarely reported from Iran …”
Section: Discussionmentioning
confidence: 97%
“…However, lower rates of other genotypes have also been reported in Eastern Azerbaijan, Northwest Iran (33). Attaullah demonstrated that genotype D (35.67%) is the predominant genotype among Afghani population, followed by genotype C (32.16%), genotype A (19.30%), and genotype B (7.02%), respectively (34). Due to the proximity of Southern Khorasan to Afghanistan, and the substantial immigration of Afghani people through this province, our results are interesting and may contribute to the social and cultural behavior, as well as the health level.…”
Section: Discussionmentioning
confidence: 99%
“…1 HBsAg endemicity in 1990-2013 and geographic distribution of HBV genotypes in Asia. The prevalence data are retrieved from a systematic review [1]; this map is prepared according to the literature [1,6,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] HBV genotypes and response to antiviral therapy in Asia HBV genotypes and response to interferon (IFN)-based therapies HBV genotypes are significantly associated with sustained response to IFN-based therapies. In general, for HBeAgpositive patients, the probability of sustained response is in a descending order from genotype A-D [50].…”
Section: Hbv Genotypes and Clinical Manifestation In Asiamentioning
confidence: 99%